Skeletal and Dental Outcomes after Facial Allotransplantation: The Cleveland Clinic Experience and Systematic Review of the Literature. Issue 4 (18th February 2022) - Coombs, Demetrius M.; Bassiri Gharb, Bahar; Tuncer, Fatma B.; Djohan, Risal S.; Gastman, Brian R.; Bernard, Steven L.; Schwarz, Graham S.; Gurunian, Raffi; Siemionow, Maria Z.; Papay, Frank A.; Rampazzo, Antonio
Abstract : Background: Most of the literature surrounding face transplantation focuses on technique, immunology, and psychology. Dental and skeletal outcomes remain persistently underreported. This study critically examined the worldwide face transplant experience to evaluate such outcomes. Methods: A systematic review of all composite allografts containing midface and/or mandible was performed. Dental and skeletal complications were recorded. Formal imaging and photographs available in the literature were analyzed using skeletal measurements, soft-tissue cephalometrics, and the Angle classification. Outcomes of our face transplant patients, including condylar assessment and airway volume measurements, is also presented. Results: Twenty-five patients received allografts containing midface ( n = 7) or mandible ( n = 2), whereas 16 contained a double-jaw. All midface-only transplants developed skeletal deformity; 57 percent developed a palatal fistula. Both partial and full arch transplantation patients developed skeletal deformity. Among double-jaw transplants, 69 percent developed palatal fistula or floor-of-mouth dehiscence, 66 percent developed malocclusion, 50 percent developed trismus, and 31 percent required corrective orthognathic surgery. In 40 percent of patients, malocclusion recurred after corrective orthognathic surgery. Forty percent of all patients developed dental cavities or periodontal disease. All of our patients received midface and/or mandible. One patient required corrective orthognathic surgery. Midfacial segments showed clockwise rotation. Airway volumes decreased over time. Conclusions: Skeletal and dental complications remain extremely common after facial allotransplantation involving either single- or double-jaw composites. Corrective orthognathic surgery and dental extraction is often necessitated. These data will aid face transplant teams during surgical planning and preoperative counseling. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, V.